A comparison of toxicities in acute myeloid leukemia patients with and without renal impairment treated with decitabine. (June 2018) - Levine, Lauren B; Roddy, Julianna VF; Kim, Miryoung; Li, Junan; Phillips, Gary; Walker, Alison R
Purpose: There are limited data regarding the clinical use of decitabine for the treatment of acute myeloid leukemia in patients with a serum creatinine of 2 mg/dL or greater. Methods: We retrospectively evaluated 111 patients with acute myeloid leukemia who had been treated with decitabine and compared the development of toxicities during cycle 1 in those with normal renal function (creatinine clearance greater than or equal to 60 mL/min) to those with renal dysfunction (creatinine clearance less than 60 mL/min). Results: Notable differences in the incidence of grade ≥3 cardiotoxicity (33% of renal dysfunction patients vs. 16% of normal renal function patients, p  = 0.042) and respiratory toxicity (40% of renal dysfunction patients vs. 14% of normal renal function patients, p  = 0.0037) were observed. The majority of heart failure, myocardial infarction, and atrial fibrillation cases occurred in the renal dysfunction group. The odds of developing grade ≥3 cardiotoxicity did not differ significantly between patients with and without baseline cardiac comorbidities (OR 1.43, p  = 0.43). Conclusions: This study noted a higher incidence of grade ≥3 cardiac and respiratory toxicities in decitabine-treated acute myeloid leukemia patients with renal dysfunction compared to normal renal function. This may prompt closer monitoring, regardless of baseline cardiac comorbidities. Further evaluation of decitabine in patients with renal dysfunction is needed.